Safety critical systems handbook : a straightforward guide to functional safety: IEC 61508 (2010 edition) and related standards : including: Process IEC 61511, Machinery IEC 62061 and ISO 13849 /: a straightforward guide to functional safety: IEC 61508 (2010 edition) and related standards : including: Process IEC 61511, Machinery IEC 62061 and ISO 13849. (2011) - Unknown
No abstract available